Safer Linux Kernel Modules Using the D Programming Language - Constantin Eduard Staniloiu; Alexandru Militaru; Razvan Nitu; Razvan Deaconescu (IEEE Access, 2022)
Since its creation, the Linux kernel has gained international recognition and has been employed on a large range of devices: servers, supercomputers, smart devices and embedded systems. Given its popularity, the security of the kernel has become a critical research topic. As a consequence, a wide range of third party tools were created to detect bugs in its implementation. However, new vulnerabilities are discovered and exploited every year. The explanation for this phenomenon lies in the fact that the programming language that is used for the kernel implementation, C, is designed to allow unsafe memory operations. In this paper, we show that it is possible to incrementally transition the kernel code from C to a memory safe programming language, D, by porting and integrating a device driver. In addition, we propose a series of code transformations that allow the D compiler to reason about the safety of certain memory operations. Our implementation increases the security guarantees of the kernel without incurring any performance penalties.